STUDI SISTEM PELAYANAN ADMINISTRATIF PENANGANAN KASUS RUJUKAN PERSALINAN KOMPLIKASI IBU BERSALIN PESERTA BPJS DI RSUD KOTA SEMARANG - Chusna Meimuna (Jurnal Kesehatan Masyarakat (Undip), 2015)
System administrative management is performed at a stage when the patient register to get right handling. Maternal who performed the referral is a patient who experienced very serious condition that requires immediate treatment but if the patient is experiencing administrative problem will have an impact of serious condition. Preface studies shows that administrative management experiencing difficult condition throughout registration process. The purpose of this research is to describe input aspect or aspects of the process in the administrative management handling referred case for childbirth complication within BPJS participant in General Hospital Semarang. This research was conducted at the administrative officers in General Hospital Semarang using quantitative methods of in-depth interviews with 11 informants consists of 5 main informants and 6 triangulation informants. The results show the input aspect that the number of administrative officer in administration services still insufficient. Result of the research shows in the input aspect, the availability of administrative officer still not sufficient because administrative mobility is too high. Training sessions in the hospital for administrative officer are not yet available. Facilities and infrastructure for some tools have not been updated such as printer and computer. There are standard procedures for personnel services in the form of job description. In the aspect of the process that is already available for the meeting of administrative officer to discuss changes to the rules or policies that are in the hospital. Lack of coordination among officers because of age factor. In the implementation of existing division of labor, each officer has their own duty and responsibility. And to supervise the administration officer have been done by the chief of each room. It can be concluded that the administrative management of the resource needs improvement, facilities and infrastructure.